ANALYSIS OF GOVERNANCE SECURITY MANAGEMENT INFORMATION SYSTEM USING INDEX KAMI IN CENTRAL GOVERNMENT INSTITUTION - Hambali, Hambali; Musa, Purnawarman (Sekolah Tinggi Teknologi Adisutjipto, 2020)
Information security is very vulnerable to institutions if there is interference from other parties outside the organization or institution as a supply chain of services that can pose an information security risk. Based on the Regulation of the Minister of Communication and Information Technology number 4 of 2016, the Electronic System organizers that operate Low Electronic Systems must apply the Information Security Index guidelines. Index KAMI are a tool in analyzing and evaluating the level of information security based on the criteria in organizations or in government institutions. The research objective is to measure the level of information security readiness that meets the requirements of the ISO/IEC27001: 2013 standard at the Central Government Institution Unit X. The results of the assessment with the index KAMI obtained an electronic system category score of 30, for the assessment of governance the score is 84, the risk management score is 35, the framework information security work value is 61, asset management 128, and the application of security and information technology has a value of 100, the level of information security maturity is level II+ with a value of 408, the results obtained up to the Compliance of the Basic Framework.